WATER BALANCE SIMULATION FOR COFFEE CROP IN TWO REGIONS OF THE MINAS GERAIS STATE, BRAZIL - SOUZA, Jorge Luiz Moretti de; FRIZZONE, José Antônio (Scientia Agraria, 2007)
The objective of this work was to simulate and to evaluate the values of crop evapotranspiration (ETc), irrigation (I), real evapotranspiration (RE) and water deficit (WD) of the coffee crop, in a decade climatic water balance model applied for irrigation, when the coffee crop and irrigation parameters were submitted to variations. The analyses were accomplished along four years of the coffee crop development, in the Lavras and Uberlândia regions, Minas Gerais state, Brazil. The results obtained with the model showed that: (a) In the years “implantation”, 1-2 and 2-3, the values of the ETc were 35%, 20% and 10% smaller than the values for adult plants, respectively; (b) Considering the probable precipitation at the 75 percent level (P75%), only the year of the implantation did not present risk with WD > 200 mm×year–1; (c) Due the occurrence of water deficiency and the coffee fenological phase, special attention should be given to the irrigations applied from March to May in Lavras, and from May to June and September to October in Uberlândia; (d) To apply 220 mm×year–1 to 382 mm×year–1 of irrigation it was necessary 7 to 8 irrigations×year–1.